f(n) is the nth term
Each term f(n) is found by adding the terms just prior to the nth term. Those two terms added are f(n-1) and f(n-2)
The term just before nth term is f(n-1)
The term just before the (n-1)st term is f(n-2)
----------------
For example, let's say n = 3 indicating the 3rd term
n-1 = 3-1 = 2
n-2 = 3-2 = 1
So f(n) = f(n-1) + f(n-2) turns into f(3) = f(2) + f(1). We find the third term by adding the two terms just before it.
f3) = third term
f(2) = second term
f(1) = first term
Answer:
Choice B is correct.
Explanation:
The given equation is -r+5(r+2)=-10
Put r=-5 into the above equation
-(-5)+5(-5+2)=-10
5+5(-3)=-10
5-15=-10
-10=-10
Right and left side of above equation is equal by putting r=-5 so it is true statement.
if x-2 is a factor of polynomial, f (×) ,then it means we can find the zeros or the solutions of the polynomial by putting for (×-2)=0 . Because the zeros or roots of a polynomial is found by putting f (×)=0 , where x is a factor of the polynomial
Answer:
4 3/8
Step-by-step explanation:
4 and 7/8 - 1/2 = 4 and 7/8 - 4/8 = 4 and 3/8 of a box more